A “3S+f” Nephrometry Score System to Predict the Clinical Outcomes of Laparoscopic Nephron-Sparing Surgery - Zhang, Shudong; Qin, Zijian; Bi, Hai; Tao, Liyuan; Zhang, Fan; Zhang, Hongxian; Wang, Wei; Wu, Jitao; Huang, Yi; Ma, Lulin (Frontiers in Oncology, 2022)
Background When we treat renal cell carcinoma by laparoscopic nephron-sparing surgery (NSS), it is essential to use an evaluation system to predict clinical outcomes. Hitherto, there are more than a dozen nephrometry score systems. In this study, through assessing the correlations between nephrometry score systems and clinical outcomes, we aim to provide a novel nephrometry score system—the “3S+f” score system—to simplify the evaluation of technical complexity of partial nephrectomy. Methods We retrospectively collected the data of 131 patients who underwent NSS, which was performed by a single surgeon (SZ) from January 2013 to July 2018 at Peking University Third Hospital. The “3S+f” score system contains four parameters: “size, side, site, and fat”, all of which can be obtained from preoperative imaging data. We evaluated the correlations between the “3S+f” score and clinical outcomes, and compared R.E.N.A.L. score and PADUA score. Results All the three nephrometry score systems were related to some clinical outcomes in univariate analyses. In multivariate regression models, the “3S+f” score, the R.E.N.A.L. score, and the PADUA score were significantly associated with operative time (p = 0.016, p = 0.035, and p = 0.001, respectively) and warm ischemia time (all p = 0.008, p < 0.001, and p < 0.001, respectively). “3S+f” was also significantly related to extubation time > 5 days (p = 0.018). In predicting operative time > 120 min and extubation time >5 days from ROC curves, the AUCs of the “3S+f” score (0.717 and 0.652, respectively) were larger than both the R.E.N.A.L (0.598 and 0.554, respectively) and PADUA (0.600 and 0.542, respectively) score systems. Conclusion A novel nephrometry score system—the “3S+f” score system—shows equivalent correlation and the ability in predicting clinical outcomes when compared to the R.E.N.A.L. score system and the PADUA score system, which can describe renal tumors.